INTERSTELLAR WATER IN METEORITES? - Deloule E.; Robert F. (My University, 1995)
D/H ratios of two meteorites (Renazzo CR and Semarkona LL3), which are known to exhibit the largest departures from the terrestrial hydrogen isotopic ratios, have been determined with the CRPG Nancy ion microprobe. Correlations between the D/H ratios and the chemical compositions (H2O, K, Si, C/H) of plausible hydrogen carriers were observed. From these correlations, it is possible to show that, contrary to previous interpretations, phyllosilicates are the carriers of the deuterium-rich hydrogen in Semarkona and Renazzo: 870 x 10-6 =< D/H =< 670 x 10-6 (+4600 =< δD =< 3300%%) and =< 320 x 10-6 (δD =< 1050%%), respectively. Hydrogen is also present in the chondrules of these two deuteriumrich meteorites. The large differences in D/H ratios between matrix (up to 700 x 10-6, δD up to +3500%%) and chondrules (from 120 x 10-6 (δD = -230%%) to 230 x 10-6 (δD = +475%%)) show that hydrogen in chondrules cannot originate from the matrix by simple contamination or diffusion processes.The high D/H ratios measured in water-bearing minerals could not have been produced thermally within a dense solar nebula. Chemical reactions (i.e., involving ions or radicals), taking place in interstellar space or in the outer regions of the nebula at 110-140 K are presently the only conceivable mechanisms capable of yielding such isotopic enrichments. Water in these meteorites should no longer be considered as a simple product of nebular condensation under equilibrium thermodynamic conditions at T =< 160 K.